The revised global yellow fever risk map and recommendations for vaccination, 2010: consensus of the Informal WHO Working Group on Geographic Risk for Yellow Fever - Jentes, Emily; Poumerol, Gilles; Gershman, Mark D; Hill, David R; Lemarchand, Johan; Lewis, Rosamund F; Staples, J Erin; Tomori, Oyewale; Wilder-Smith, Annelies; Monath, Thomas P (The lancet. Infectious diseases, 2011)
The changing epidemiology of yellow fever and continued reports of rare but serious adverse events associated with yellow fever vaccine have drawn attention to the need to revisit criteria for the designation of areas with risk for yellow fever virus activity, and to revise the vaccine recommendations for international travel. WHO convened a working group of international experts to review factors important for the transmission of yellow fever virus and country-specific yellow fever information, to establish criteria for additions to or removal from the list of countries with risk for yellow fever virus transmission, to update yellow fever risk maps, and to revise the recommendations for vaccination for international travel. This report details the recommendations made by the working group about criteria for the designation of risk and specific changes to the classification of areas with risk for transmission of yellow fever virus.
Gesehen am 05.07.2022